Relative velocity based vehicle–to–vehicle routing protocol over ad–hoc networks. (15th January 2013) - Lee, Won–Il; Pyun, Jae–Young; Lee, Yang Sun; Lee, Sang–Woong
In this paper, we introduce a new routing protocol supporting high mobility over VANET which is using hop counts and relative velocity between vehicles to find the best routing transmission path. By exchanging vehicles' relative velocities, the more stable and reliable paths are searched as compared to traditional MANET protocols using only hop count information at the time of routing path set–up. To evaluate proposed routing protocol, we compared it with original Ad hoc On–demand Multipath Distance Vector (AOMDV) on NS2. The simulation results showed that proposed routing protocol achieves better performance from about 10% to 50% in terms of normalized routing overhead and packet delivery ratio, when video sequences are transferred on channels. The proposed routing protocol can be useful for the Vehicle–to–Vehicle (V2V) transmission of traffic monitoring data, audio, and video streaming services without the additional global position devices.